Negros, profissionais e acadêmicos: sentidos identitários e os efeitos do discurso ideológico do mérito - Miranda, Sheila Ferreira (2013)
The effects of intergenerational transmission of poverty perpetuated by discrimination, support today, the persistence of the confinement of the black segment to the lower strata and the subsequent alienation of these individuals from access to quality education in the Brazilian context. When the possibilities for the integration of the blacks into the category of academic professionals are considered, we realize that the Brazilian higher education institutes provide alarmingly racist quantitative indices, buffered by a justificatory discourse which, tied to the ideal of meritocracy and to the apology of competence, overshadow, in ideological terms, the dimensions brought by the effects of racial discrimination. Therefore, we set out to try to understand the directions given to the condition of being black in the university and thus, six oral history interviews with individuals who seek or are already inserted in such academic context were performed. It was concluded that we are facing a problem which bring us to the context of identity of such individuals, who even after their admission to the universities, are impelled to assert themselves permanently, both as professionals in the academy, and as black academic professionals. However, it was also analyzed that the energy of individual projects of transformation, the echoes of collective militancy and the instituting forces of the university can lead to multiple emancipatory possibilities. Due to all these issues above, we defend the thesis of the impossibility of discussing the lack of blacks in the university teaching system, when performed only under the assumptions of personal qualification and merit, which also implies the introduction of a debate in favor of the expansion of the quota system to higher strata within the Brazilian academic context